Rice reimagined: Enhancing nutritional value and glycemic control through fortified parboiled rice / Nisa Rosyidah, Nurhayati and Septi Afifah - Rosyidah, Nisa; hayati, Nur; Afifah, Septi (2024)
Rice (oryza sativa l.) is one of the essential foods and a major source of energy-nutrients for the global population. Rice production is about 480 million metric tons per year, with major contributions from Asia, accounting for more than 90% of global production and 88% of consumption. Despite rice being a source of energy, the process of refining rice removes essential vitamins and minerals, resulting in an increased risk of nutritional deficiencies in populations that consume rice as a staple food. More than 870 million people worldwide suffer from chronic nutritional deficiencies, especially in developing countries. In addition, rice has a high glycemic index (GI) of >73, which causes high blood sugar spikes (hyperglycemia) and increases the risk of obesity and type-2 diabetes. Replacing high-glycemic-index white rice with low-glycemic-index white rice is fundamental due to the surge in obesity and diabetes. Globally, every 5 seconds, one person dies of diabetes, and at the national level diabetes is the third leading cause of death. The needed alternative is medical rice, rich in nutrients with a low glycemic index (GI) <55. Rice bran, as a by-product of rice milling, can be a potential solution due to its high content of nutrients and functional compounds. Parboiling and fortification methods in rice can be used to improve the nutritional quality of rice and lower the glycemic index of rice. Parboiling increases the absorption of rice bran nutrients into the rice, while fortification adds polyphenols and essential nutrients, resulting in nutrient-rich rice with a low glycemic index. The results show that fortified parboiled rice has a high nutrient content and lower glycemic index.